Assessment of CardiOvascular Remodelling following Endovascular aortic repair through imaging and computation: the CORE prospective observational cohort study protocol - Nauta, Foeke J H (BMJ Open, 2016)
INTRODUCTION: Thoracic aortic stent grafts are orders of magnitude stiffer than the native aorta. These devices have been associated with acute hypertension, elevated pulse pressure, cardiac remodelling and reduced coronary perfusion. However, a systematic assessment of such cardiovascular effects of thoracic endovascular aortic repair (TEVAR) is missing. The CardiOvascular Remodelling following Endovascular aortic repair (CORE) study aims to (1) quantify cardiovascular remodelling following TEVAR and compare echocardiography against MRI, the reference method; (2) validate computational modelling of cardiovascular haemodynamics following TEVAR using clinical measurements, and virtually assess the impact of more compliant stent grafts on cardiovascular haemodynamics; and (3) investigate diagnostic accuracy of ECG and serum biomarkers for cardiac remodelling compared to MRI. METHODS AND ANALYSIS: This is a prospective, nonrandomised, observational cohort study. We will use MRI, CT, echocardiography, intraluminal pressures, ECG, computational modelling and serum biomarkers to assess cardiovascular remodelling in two groups of patients with degenerative thoracic aneurysms or penetrating aortic ulcers: (1) patients managed with TEVAR and (2) control patients managed with medical therapy alone. Power analysis revealed a minimum total sample size of 20 patients (α=0.05, power=0.97) to observe significant left ventricular mass increase following TEVAR after 1 year. Consequently, we will include 12 patients in both groups. Advanced MRI sequences will be used to assess myocardial and aortic strain and distensibility, myocardial perfusion and aortic flow. ECG, echocardiography and serum biomarkers will be collected and compared against the imaging data. Computational models will be constructed from each patient imaging data, analysed and validated. All measurements will be collected at baseline (prior to TEVAR) and 1-year follow-up. The expected study period is 3 years. ETHICS AND DISSEMINATION: This study has been approved by the University of Michigan IRB. The results will be disseminated through scientific journals and conference presentations. TRIAL REGISTRATION NUMBER: NCT02735720.